EBV Viral Loads in Diagnosis, Monitoring, and Response Assessment - Kimura, Hiroshi; Kwong, Yok-Lam (Frontiers in Oncology, 2019)
The quantification of circulating Epstein Barr virus (EBV) DNA loads has played an important role in the diagnosis and management of EBV-associated lymphoid malignancies. Viral load measurement is particularly useful for monitoring EBV-DNA in hematopoietic stem cell transplant patients, and for assessing the prognosis or response to therapy of EBV-associated intractable lymphomas like extranodal NK/T-cell lymphoma, nasal type. Cell-free EBV-DNA in plasma can be used as a biomarker for estimating the severity or prognosis of these lymphomas. In addition to plasma, whole blood has been used for the management of transplant patients. Although measuring EBV-DNA has been useful, there is a lack of standardization and the optimal specimens for measuring viral loads are unknown. This can be attributed to the different forms of EBV-DNA that exist in peripheral blood and the different pathologies that result from diverse EBV disease states. As a result, guidelines for EBV diagnosis or the initiation of treatment are unclear. However, the newly established World Health Organization standard for EBV quantification will encourage collaborative studies across institutions and countries to establish proper guidelines for EBV diagnosis and the initiation of treatment.